Electrochemical Design of Gold Nanostructures for Controllable Electrochemical Performance and Scalable Aptamer Sensing Application - Chen, Feixiong; Mostafiz, Bahar; Suni, Johanna; Peltola,Emilia (American Chemical Society, 2025)
A simple electrochemical method for designing gold nanostructures was developed by programming deposition potentials, enabling surface nanoengineering of screen-printed electrodes. As a result of this method, we have observed three distinct growth modes of gold nanostructures, which, depending on their various morphologies, are Needle-shaped gold nanostructures (one dimensionally dominated mode), leaf-shaped gold nanostructures (two-dimensionally dominated mode), and coral-shaped gold nanostructures (three-dimensionally dominated mode). All gold nanostructures exhibited an enhanced electrochemical response to the redox solution, improved reversibility, and reduced impedance, compared to the unmodified electrodes, albeit to varying degrees. We demonstrated the superior antifouling performance of the coral-shaped gold nanostructures in a redox solution containing bovine serum albumin, compared to other gold nanostructures. Finally, to assess another aspect of differences in the electrochemical sensing behaviors, we constructed an aptamer sensor for progesterone detection, where the needle-shaped gold nanostructures showed the highest signal gain using Electrochemical Impedance Spectroscopy, in comparison to that of leaf-shaped and coral-shaped gold nanostructures. We envision that the proposed method will potentially enable the design or fabrication of desirable gold nanostructures with increasingly complex or hierarchical structures, bearing promising applications in wide sensing and biomedical applications.